Emergent cultural phenomena and their cognitive foundations - Christian Cordes (Max Planck Institute of Economics, 2007)
To explain emergent cultural phenomena, this paper argues, it is inevitable to understand the evolution of complex human cognitive adaptations and their links to the population-level dynamics of cultural variation. On the one hand, the process of cultural transmission is influenced and constrained by humans' evolved psychology; people tend to acquire some cultural variants rather than others. On the other hand, the cultural environment provides cultural variants that are transmitted to or adopted by individuals via processes of social learning. To gain insights into this recursive relationship between individual cognitive dispositions at the micro level and cultural phenomena at the macro level, the theory of gene-culture coevolution is applied. Moreover, a model of cultural evolution demonstrates the dissemination of novelty within a population via biased social learning processes. As a result, some unique facets of human behavior and cumulative cultural evolution are identified.
Keywords: 330; Cultural Evolution; Social Learning; Diffusion Dynamics; Coevolution; Evolutionary Economics; Kulturpsychologie; Evolutionsökonomik; Kognition; Sozialer Wandel; Lernprozess; Theorie